SUPERVISI KEPALA MADRASAH DALAM MENINGKATKAN KEDISIPLINAN GURU DI MADRASAH TSANAWIYAH MATHOLIUL FALAH KANDANGMAS DAWE KUDUS TAHUN PELAJARAN 2024/2025: Studi Kualitatif di MTs Matholiul Falah Kudus - Imam Sofi’i; Subaidi; Sukarman (Rihlah Review: Jurnal Pendidikan Islam, 2025)
This study was conducted at Madrasah Tsanawiyah Matholiul Falah Kandangmas Dawe Kudus Academic Year 2024/2025. This study is a descriptive qualitative research. Data was collected through observation, interviews, and documentation. The data was then analyzed through four stages: data collection, data reduction, data presentation, and conclusion drawing, The results of this study show that (1) the headmaster's supervision plays a role in enhancing teacher discipline by providing oversight, support, and direction to teachers in the teaching and learning process. The head of the madrasah carries out indirect supervision, namely by providing guidance and direction in a forum together or in groups. In addition, supervision is carried out directly using individual techniques, namely class visits. (2) The supporting factors for enhancing teacher discipline through supervision are adequate facilities, salaries, comfortable work environment, good communication between teachers and supervisors, and teachers' awareness of improving their discipline. The inhibiting factors are limited time, the headmaster's many activities, and teachers' absence during scheduled supervision. (3) The follow-up actions taken by the headmaster to improve teacher discipline include providing evaluation feedback, individual and group coaching, involving teachers in training, and coordinating with teachers to improve supervision evaluation results